A ballbar test for measurement and identification the comprehensive error of tilt table. (April 2016) - Chen, Jian-xiong; Lin, Shu-wen; Zhou, Xiao-long; Gu, Tian-qi
Abstract: This paper proposes a comprehensive geometric error measurement and identification method for a tilt table equipped in a five-axis machine tool with two turntables using the double ballbar. Three positional errors of the socket, caused by both the volumetric error and linkage error of the tilt table, are measured in the sensitive directions with simple circular paths. A mathematics model is applied to map the relationship between the night results that are from three installation positions of the socket and all the errors of the tilt table. Firstly, all the measured results are applied to establish the average axis that is just with the linkage error of the tilt table using the newly developed circular fitting method, rather than solving the large-scale linear equations. Then, the linkage error is treated as the trend item in the measured results for it keeps constant during the rotation of the tilt table. Hence, the volumetric error is identified by the remaining part of the measured results, which are obtained by subtracting the part caused by the linkage error, using the pseudo invert matrix method. Meanwhile, an error model is established to analyze the influence of the installation errors of the socket and the tool cup. Two simple correction procedures, using a low-cost electron clamp and an easily operated circular path, are developed to eliminate these two installation errors before the ballbar test. Finally, a verification experiment, by comparing the predicted value from the identified errors with the measured results by the ballbar, is carried out to validate the effectiveness and correctness of the proposed method. Highlights: A comprehensive geometric error measurement method for tilt table using ballbar. A robust linkage error identification model using the circular fitting method. Both linkage and volumetric errors are recognized from the same measured results. A simple measurement procedure with a series of circular paths. A comprehensive correction procedure to diminish the ballbar installation errors.